Odpowiedź :
[(3x-5)/(2x-1)]+[(2x-7)/(1-2x)]=3
zał.
2x-1≠0
x≠1/2
D=R/{1/2}
[(3x-5)/(2x-1)]-[(2x-7)/(2x-1)]=3
[(3x-5)-(2x-7)]/(2x-1)=3 /*(2x-1)
3x-5-2x+7=3(2x-1)
x+2=6x-3
-5x=-5
x=1∈D
zał.
2x-1≠0
x≠1/2
D=R/{1/2}
[(3x-5)/(2x-1)]-[(2x-7)/(2x-1)]=3
[(3x-5)-(2x-7)]/(2x-1)=3 /*(2x-1)
3x-5-2x+7=3(2x-1)
x+2=6x-3
-5x=-5
x=1∈D
(3x-5)/(2x-1) + (2x-7)/(1-2x)=3
-3x+5/(1-2x) + 2x-7/(1-2x)=3
-x-2/(1-2x)=3
Sorka dalej nie umie ale jak coś wykombinuje to napisze pozdro
-3x+5/(1-2x) + 2x-7/(1-2x)=3
-x-2/(1-2x)=3
Sorka dalej nie umie ale jak coś wykombinuje to napisze pozdro